Analisis intensi membayar zakat berdasar planned behaviour approach (Studi pada Lazis Baitul Arqam Purwokerto) - Wahyudin Wahyudin; Siti Zulaikha Wulandari; Larisa Pradisti (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2018)
Islam has taught its people to live together and help each other, through worship such of zakkah, infaq, shadaqoh (ZIS). Zakkah as the fifth pillar of Rukun Islam is one form of wealth transfer from the rich to the poor which is in need, in accordance with the sharia of Islam. In the Theory of Planned Behaviour (TPB), a person's intention to behave (behavioral intention) is influenced by attitudes toward the behavior, subjective norms that influence the behavior and perceived behavioral control. This study intends to examine the effect of attitude toward behavior, subjective norm, and perceived behavioral control on the muzaki’s intention to behave in paying zakat. Measurement of intention to behave can be a best way to predict future behavior. By knowing this, Zakkah institution managers can predict customer behavior in order to determine the best  strategy. Research shows that attitudes toward behavior, Subjective Norms and Behavioral Control has a significant influence on Muzaki’s intention to pay zakat. Eserch results show that among the three variables studied, it is known that the behavioral control X3) is the most influential variable on behavior intention compare to attitude toward behavior (X1) and Subjective Norm (X2).Keywords:  zakat, planned behaviour approach, purwokerto.